ANALISIS YURIDIS TERHADAP PEMBATALAN MEREK DALAM KONTEKS PERSAMAAN POKOK DENGAN MEREK TERDAFTAR - Hardina, Tati Sri; F.R, Mella Ismelina (Universitas Ekasakti, 2023)
In the trademark, the term First to file system is known to grant rights to the brand. Under the First to file system, trademark owners, including well-known marks, must register their trademarks at the Directorate General of Intellectual Property (“DJKI”) to obtain exclusive rights to their trademarks and legal protection. Exclusive rights cannot be obtained by the owner of the mark only by showing evidence that he is the first user of the mark in Indonesia. The first-to-file system means that the party who first applies for registration is given priority to get the trademark registration and is recognized as the rightful owner of the mark. This principle is explicitly regulated in Article 3 of Law Number 20 of 2016 concerning Marks and Geographical Indications (“MIG Law”) which stipulates that rights to a mark are obtained after the mark is registered.. In writing this study, the author uses a type of normative research, namely legal research which is carried out by examining primary legal materials and secondary legal materials. Based on the considerations, the panel of judges is of the opinion that the claimant's claim has legal grounds to be granted for some of which will be stated in the verdict, in the conference, the exception stated that Defendant I's exception is unacceptable, in the main matter of the case rejecting the Plaintiff's claim, Ruben Samuel Onsu, in its entirety. . In the reconpension the counterclaims granted by the Plaintiff for reconsideration of PT Ayam Geprek Benny Sujono partially and stated that the Plaintiff of the Counterclaim was the owner and first legal user of the Mark “I AM GEPREK BENSU SEDEP BENEERRR + LUKISAN”. Declared null and void with all the legal consequences of registering a trademark in the name of Ruben Samuel Onsu, rejecting the claim of the Reconvention Plaintiff other than and the rest.